2021
DOI: 10.3390/ijms222413528
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine Systems at the Crossroads of Inflammation and Energy Metabolism in the Development of Obesity

Abstract: Obesity is characterized as a complex and multifactorial excess accretion of adipose tissue accompanied with alterations in the immune and metabolic responses. Although the chemokine systems have been documented to be involved in the control of tissue inflammation and metabolism, the dual role of chemokines and chemokine receptors in the pathogenesis of the inflammatory milieu and dysregulated energy metabolism in obesity remains elusive. The objective of this review is to present an update on the link between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…Lastly, we studied the mRNA expression of genes coding for chemokines that contribute to the inflammatory processes by recruiting immune cells and prompting the latter to generate pro-inflammatory signals. With regard to the mRNA expression of standard markers of macrophage recruitment (MCP1, CCL5, and CXCL10), T cell recruitment (CX3CL1 and CXCL10) and NK cell recruitment (CX3CL1), we did not observe any significant changes in SIV+ animals versus SIV− animals [39,40]. Although the significant difference in MCP1 expression have been widely reported in the context of obesity [41], we In summary, we detected few differences in the AT's production of these two cytokines following infection.…”
Section: The Inflammatory Profile Of Atmentioning
confidence: 58%
“…Lastly, we studied the mRNA expression of genes coding for chemokines that contribute to the inflammatory processes by recruiting immune cells and prompting the latter to generate pro-inflammatory signals. With regard to the mRNA expression of standard markers of macrophage recruitment (MCP1, CCL5, and CXCL10), T cell recruitment (CX3CL1 and CXCL10) and NK cell recruitment (CX3CL1), we did not observe any significant changes in SIV+ animals versus SIV− animals [39,40]. Although the significant difference in MCP1 expression have been widely reported in the context of obesity [41], we In summary, we detected few differences in the AT's production of these two cytokines following infection.…”
Section: The Inflammatory Profile Of Atmentioning
confidence: 58%
“…GSEA reveals that, before bariatric surgery, most genes are predominantly enriched in chemokines, TOLL-like receptor, and B cell receptor signaling pathways-mechanisms integral to adipose tissue in ammation. Adipocytes release chemokines that intensify tissue in ammation, with speci c chemokines like CCL2 and CCL5 exacerbating systemic in ammation by recruiting proin ammatory M1 macrophages, thereby contributing to obesity and its chronic complications [21]. Toll-like receptor signaling induces fatty acid synthesis, fostering chronic in ammation in adipose tissue and contributing to the metabolic syndrome associated with obesity [22].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have reported that the deficiency of M1 macrophages enhances insulin sensitivity in obese mice [ 38 ], whereas deletion of M2 macrophages results in insulin resistance in wild-type (WT) mice [ 38 ]. Obesity induces upregulated expression of chemokines such as MCP-1 (monocyte chemoattractant protein-1, CCL2) and CCL5 (C-C Motif Chemokine Ligand 5) in order to recruit M1 macrophages to adipose tissues [ 39 ]. These recruited M1 macrophages secrete pro-inflammatory cytokines, including TNF, IL-6, and IL-1β, and oxidative metabolites such as superoxide and nitric oxide (NO), resulting in inflammation and insulin resistance [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%